1999
DOI: 10.1046/j.1365-294x.1999.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microsatellite loci in the aphid species Aphis gossypii Glover

Abstract: polymorpha individuals as D. bugensis. The high species specificity of these new microsatellite markers will help to minimize the potential error associated with such complications. ReferencesBaldwin BS, Black M, Sanjur O et al. (1996) A diagnostic molecular marker for zebra mussels (Dreissena polymorpha) and potentially co-occurring bivalves: mitochondrial COI. Molecular Marine Biology and Biotechnology, 5, 9Ð14. Claxton WT, Martel A, Dermott RM, Boulding EG (1997) Discrimination of field-collected juveniles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 1 publication
1
54
0
Order By: Relevance
“…The genetic diversity found in A . gossypii through the use of molecular markers has shown that the clonal diversity is structured by its host plant 34, 35 . In the present study, A .…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity found in A . gossypii through the use of molecular markers has shown that the clonal diversity is structured by its host plant 34, 35 . In the present study, A .…”
Section: Discussionmentioning
confidence: 99%
“…Adult female aphids collected from the five host plants were genotyped based on the seven microsatellite loci Ago24, Ago53, Ago59, Ago66, Ago69, Ago84, and Ago89 (40). The 106 aphids collected in the wild belonged to just four genotypes (genotypes I to IV) ( Table 2), and the genetic similarity of these four genotypes was 28 to 44% based on these seven loci.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA was diluted 10-fold and stored at -20°C. PCR was performed using 10 μL of the reaction mixture, containing 6 μL of 2× PCR Master Mix (Jena BioScience GmbH, Jena, Germany), 1 μL (10 pM) of each forward and reverse primer (Ago89, Ago66, Ago24, Ago59, Ago53, Ago84, Ago69, Ago126) (VanlerbergheMasutti et al, 1999) and 1.5 μL of aphid template DNA (approximately 10 ng), using the following cycling parameters: initial denaturation at 94°C for 5 min followed by 35 cycles of denaturation at 94°C for 1 min, locus-specifi c annealing temperature 1 min according to Vanlerberghe-Masutti et al (1999); and extension at 74°C for 30 s, with a fi nal extension at 74°C for 5 min. Products were separated on 6% polyacrylamide urea gel at 75 W constant power (Bio-Rad Laboratories, Hercules, CA, USA).…”
Section: Dna Extraction and Microsatellite Analysismentioning
confidence: 99%